2021
DOI: 10.3390/healthcare9080953
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Turkish University Students Addicted to the Internet? A Moderated Mediation Model

Abstract: Internet addiction has become a significant problem that primarily affects young people. It has an essential effect on the individual’s self-perception and assessment of their competencies. This study aimed to reveal whether there is a significant relationship between the level of internet addiction of university students and their age and self-esteem. For this purpose, internet addiction and self-esteem scales were used in addition to questions such as age, gender, the purpose of internet use, and internet da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
0
2
1
Order By: Relevance
“…Interestingly, the present study found no gender difference in students' scores of IA which is not consistent with many of the existing findings indicating male students tend to have a higher level of IA than female students (e.g., Anand et al, 2018;Bhandari et al, 2017;Salehi et al, 2014). Some scholars argued that the non-significant association between gender and IA may be due to the reason that the influence of gender was influenced by other demographic variables (Kocak et al, 2021) and other factors such as cultural and community values (Khan et al, 2017). Therefore, more studies should be conducted in the future to understand the interacting effect of gender with other demographic factors such as culture.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, the present study found no gender difference in students' scores of IA which is not consistent with many of the existing findings indicating male students tend to have a higher level of IA than female students (e.g., Anand et al, 2018;Bhandari et al, 2017;Salehi et al, 2014). Some scholars argued that the non-significant association between gender and IA may be due to the reason that the influence of gender was influenced by other demographic variables (Kocak et al, 2021) and other factors such as cultural and community values (Khan et al, 2017). Therefore, more studies should be conducted in the future to understand the interacting effect of gender with other demographic factors such as culture.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with the results of our study, it was determined in the literature that the age variable has a positive association with self-esteem and satisfaction with life. In contrast, it has a negative correlation with the internet and social media addiction [86][87][88][89][90][91][92]. However, in the literature, it was seen that the use of the internet and social media by the elderly to spend time, socialize, shop, and find old friends have been increasing [93,94].…”
Section: Discussionmentioning
confidence: 99%
“…participants showing lower levels of self-determination. Furthermore, Koçak et al (2021) found in a large-scale study that there is an age-related increase in self-esteem, which can be linked to SDL. The study also found that males tend to have higher self-esteem than females.…”
Section: Significance Of the Studymentioning
confidence: 99%